Non‐paraxial theory of self‐focusing/defocusing of Hermite cosh Gaussian laser beam in rippled density plasmas. Issue 10 (2nd September 2019) - Pathak, Nidhi; Kaur, Manpreet; Kaur, Sukhdeep; Gill, T. S.
Abstract: Present research work focuses on study of self‐focusing and self‐trapping of Hermite cosh Gaussian (HchG) laser beams in rippled density plasma by considering relativistic non‐linearity. The coupled non‐linear differential equations for the beam width parameters (for modes m  = 0, 1, and 2) were derived by employing higher‐order correction in comparison to paraxial ray theory by expanding dielectric function and eikonal up to r 4 terms. It is observed that the inclusion of higher‐order terms significantly influence the off‐axial properties for m  ≥ 1 mode indices. Furthermore, the effect of parameters including beam intensity, ripple factor, depth of density modulation, and decentred parameter on self‐focusing and self‐trapping is analysed and discussed both analytically and numerically.